Intronic primers reveal unexpectedly high major histocompatibility complex diversity in Antarctic fur seals - Tebbe, Jonas; Ottensmann, Meinolf; Havenstein, Katja; Efstratiou, Artemis; Lenz, Tobias L; Caspers, Barbara; Forcada, Jaume; Tiedemann, Ralph; Hoffman, Joseph (Scientific Reports, 2022)
Tebbe J, Ottensmann M, Havenstein K, et al. Intronic primers reveal unexpectedly high major histocompatibility complex diversity in Antarctic fur seals. Scientific Reports . 2022;12(1): 17933. The major histocompatibility complex (MHC) is a group of genes comprising one of the most important components of the vertebrate immune system. Consequently, there has been much interest in characterising MHC variation and its relationship with fitness in a variety of species. Due to the exceptional polymorphism of MHC genes, careful PCR primer design is crucial for capturing all of the allelic variation present in a given species. We therefore developed intronic primers to amplify the full-length 267bp protein-coding sequence of the MHC class II DQB exon 2 in the Antarctic fur seal. We then characterised patterns of MHC variation among mother-offspring pairs from two breeding colonies and detected 19 alleles among 771 clone sequences from 56 individuals. The distribution of alleles within and among individuals was consistent with a single-copy, classical DQB locus showing Mendelian inheritance. Amino acid similarity at the MHC was significantly associated with genome-wide relatedness, but no relationship was found between MHC heterozygosity and genome-wide heterozygosity. Finally, allelic diversity was several times higher than reported by a previous study based on partial exon sequences. This difference appears to be related to allele-specific amplification bias, implying that primer design can strongly impact the inference of MHC diversity. © 2022. The Author(s).